Some historiographic problems of the Hungarian history (in the context of Turkic ethnic culture) (Journal of history, 2020)
The study of the ethnic history of the Hungarian people is one of the actualis suesin historicalscience.The ancient history ofthe formation of the Hungarian people as an ethnos is undoubtedly interestingfor nomadic civilization and settled nations. Their distinctive difference from other European nationsis in their deeply rooted ethnic history. If we lookin addition at the proto-Hungarian language formed1 millennium BC, then Hungarian’s historical origin dates back to 2,500 BC. Nonetheless the first truewritten sources appear in the IX century. The close connection of this ethnos, called Magyars in generalhistory, with the nomadic Kypchaks required difficult turning points in historiography. If we look at thehistory of Magyars before the IX century, we see that they need to be considered from the point of viewof a single nomadic civilization. However, historical data on the western part of the Hungarians who settledon the banks of the Danube and Tissa were preserved only in Western chronicles. And the historicaldata on eastern hordes were found in Arab and Persian sources. However, until the present time, a largeamount of data related to Hungary is composed of Western data.